THE TAX TREATMENT OF INCOME FOR INDIVIDUALS FROM INDEPENDENT ACTIVITIES PERFORMED INDIVIDUALLY - CIUMAG MARIN; CIUMAG ANCA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
Individuals who wish to regularly and continuously conduct independent activities to generate income from production, service provision, commerce, and liberal professions can choose one of the following organizational forms: • Individually: - Authorized natural person (PFA); - Independent natural person (PFI), if they possess a recognized and authorized qualification for professional services. • In association: - As an entrepreneur holding an individual enterprise; - As a member of a family enterprise. The authorized natural person must request registration and authorization from the trade registry office of the court in the county where they establish their professional headquarters. The independent natural person submits the necessary documents to the territorial structure of A.N.A.F. for registration as an independent natural person and obtains the tax registration certificate (CIF). The determination of net income for authorized natural persons can be done, optionally, according to legal provisions [4]: • In the real system; • Based on income norms. For independent natural persons, net income is determined exclusively in the real system. The tax obligations of the authorized natural person and independent natural persons include income tax, social security contributions, and health insurance contributions. The annual net income is determined as the difference between the gross income earned and deductible expenses incurred for income generation. Reported tax losses, social security contributions, and health insurance contributions are deducted from the annual net income, resulting in the annual taxable net income. A 10% rate applies to this income to determine the income tax due.